TINDAK TUTUR DIREKTIF DALAM NOVEL PUKAT KARYA TERE-LIYE - Rizqi, Dwi Sari; Agustina, Agustina; Ngusman, Ngusman (Universitas Negeri Padang, 2013)
This article was written based on (a) to describe the type of directive speech acts, (b) the strategy told the directive speech act, (c) the context of the use of directive speech acts, and (d) the effect of the use of linguistic politeness strategies recalled toin the novelPukat created by Tere-Liye.The data of this study is the speech acts of the figures contained in the novel Pukat created by Tere-Liye.The data source of this research is the novelPukat created by Tere-Liye.Data collected by reading and noting directive speech acts contained therein. Data were analyzed with the following steps: (1) identify the data and classifies data based on type, recalled strategy, context, and tells of the effects of linguistic politeness strategies in the directive speech act, (2) connecting the data with the data of the other, (3 ) conducted a study of data inference.The findings of this study are as follows. First, there are 5 types of directive speech acts, that is telling, asking, advising, challenging, and suggest. Second, there are 3 strategies recalled, that tells directly without further ado, instantly recalled with niceties positive politeness, recalled instantly with niceties negative politeness. Third, the strategy of direct recalled without further ado tends to be used in the context of the directive speech act hearer smaller, intimate, and speech do both. Fourth, the use of recalled strategy directly without further ado hearer in the context of smaller, intimate, and the speech made ​​two decent effect.